Layanan Infromasi Asumsi Dasar Keilmuan Bimbingan dan Konseling - Offando, Ocen; Jamaris; Solfema (Universitas Nusantara PGRI Kediri, 2022)
In seeking knowledge it is impossible to be separated from a person's basic assumptions where of course there must be basic assumptions or assumptions about something. Assumptions can be interpreted as conjectures that are accepted as the basis or foundation for thinking because they are considered true, while assumptions in the philosophy of science are assumptions or basic suppositions about the reality of an object which become a study or foundation for the preparation of scientific knowledge needed in the development of science as well as in the process of giving information service. Because in the information service process a counselor needs rational and critical thinking as well as empirical knowledge and intuition so that the services provided can be received effectively. This type of research is a literature study by utilizing articles or journals related to basic scientific assumptions in the information service process.